2021
DOI: 10.1016/j.cub.2020.10.026
|View full text |Cite
|
Sign up to set email alerts
|

TORC1 Determines Fab1 Lipid Kinase Function at Signaling Endosomes and Vacuoles

Abstract: Highlights d The Fab1 lipid kinase is a substrate of the Target of Rapamycin Complex 1 (TORC1) d Fab1 and TORC1 localize to signaling endosomes and the vacuole d Fab1 phosphorylation shifts TORC1 to signaling endosomes and changes its activity d Fab1 and TORC1 function in a regulatory feedback loop, which controls signaling

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
81
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 83 publications
(134 reference statements)
10
81
0
Order By: Relevance
“…We were particularly interested in the Kog1 subunit, as it was one of our most abudant hits in the proteomics screen for Vps501 interactors (Figure 2). Similar to what others have found, we localized Kog1-2XGFP to two independent TORC1 pools; one around the vacuolar membrane and a second in dot-like perivacuolar structures (Chen et al, 2021;Hatakeyama et al, 2019)(Figure 8A). This dual localization is consistently present in wildtype, vps501∆ or sea1∆ cells.…”
Section: The Torc1 Complex and Induction Of Autophagy Are Defective In Vps501∆sea1∆ Cellssupporting
confidence: 88%
See 2 more Smart Citations
“…We were particularly interested in the Kog1 subunit, as it was one of our most abudant hits in the proteomics screen for Vps501 interactors (Figure 2). Similar to what others have found, we localized Kog1-2XGFP to two independent TORC1 pools; one around the vacuolar membrane and a second in dot-like perivacuolar structures (Chen et al, 2021;Hatakeyama et al, 2019)(Figure 8A). This dual localization is consistently present in wildtype, vps501∆ or sea1∆ cells.…”
Section: The Torc1 Complex and Induction Of Autophagy Are Defective In Vps501∆sea1∆ Cellssupporting
confidence: 88%
“…Lastly, we have defined the role of Vps501 as a co-regulator of autophagy that promotes SEACIT inhibition of TORC1 during autophagy induction. The yeast Rag GTPase-TORC1 complex is found in two spatially and functionally distinct pools, on both the vacuolar and endosomal membranes (Chen et al, 2021;Hatakeyama et al, 2019). Vacuolar TORC1 promotes protein synthesis through its proximal effector Sch9, while endosomal TORC1 controls autophagy induction through phosphorylation of Atg13, preventing Atg1 complex formation at the preautophagosomal structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results strongly suggest that the protein binds to the vacuole via its N-terminal domain (residues 1-182), while and C2 domain is dispensable (Figures 1 and S1). While this manuscript was in preparation, a study was published that confirmed our observations on the in vivo localization of Sch9 truncation mutants, and showed that the N-terminal domain of Sch9 preferentially interacts in vitro with PI(3,5)P 2 and localizes on the vacuole in vivo (Chen et al , 2021). It will be interesting to elucidate the mechanism of this interaction, since the N-terminal domain of Sch9 does not seem to correspond to any known lipid-binding domain.…”
Section: Discussionsupporting
confidence: 67%
“…These results suggest that Fab1 is an upstream component that influences vacuole fragmentation in C. neoformans ( Figure 6 ). In addition to Fab1, TORC1 is also required for vacuole fragmentation in S. cerevisiae [ 5 , 25 ]. Therefore, we tested whether TORC1 also influences vacuole fragmentation in C. neoformans by growing wild-type and sod2 mutant cells with rapamycin.…”
Section: Resultsmentioning
confidence: 99%